The Effect of the Combination of Glucose Concentration with the Type of Extenders on the Quality of Native Rooster Spermatozoa during Storage - K. Khaeruddin; Muhammad Amir (Chalaza Journal of Animal Husbandry, 2019)
This study aimed to findthe best combination of glucose concentration with the type of extender to maintain progressive motility and viability of Native Rooster spermatozoa, which stored for 48 hours at 5oC. This study used a completely randomized design (CRD) factorial pattern of 4 x 3. The first treatment was a different type of extender: LE (lactated ringer egg yolk), LS (lactated ringer skim milk), CE (coconut water egg yolk) and CS (coconut water skim milk), while second treatment was glucose concentration (20mM, 50mM, and 80mM).  Native Rooster semen diluted with a ratio of 1:10, thensperm was stored in the refrigerator (5oC). Progressive motility and viability were observed at 0, 24, 48, and 72 hours. The results showed the type of extender treatment had a very significant effect (P 0.01) on the viability of spermatozoa, which were stored 24-hour. The treatment of extender type, glucose concentration, and interaction of extender type with glucose concentration had a very significant effect (P 0.01) on the quality of spermatozoa, which were stored 48 hours and 72 hours. The highest progressive motility of spermatozoa was maintained up to 46.67 ± 2.89% and spermatozoa viability up to 74.68 ± 4.51% in WE 80mM glucose extenders, so the conclusion of this study is the combination of egg yolk coconut water with 80mM glucose is the best extender to maintain progressive motility and viability of spermatozoa of Native Rooster which is stored for 72 hours at 5oC.